2020
DOI: 10.1002/hon.2784
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next‐generation sequencing reveals molecular heterogeneity in non‐chronic lymphocytic leukemia clonal B‐cell lymphocytosis

Abstract: Non-chronic lymphocytic leukemia (non-CLL) clonal B-cell lymphocytosis (CBL) encompasses a heterogeneous group of hematologic disorders that are still poorly understood. To shed light on their biological aspects, we retrospectively analyzed a highly selected series of 28 patients, who had a clonal B-cell population in the peripheral blood and in the bone marrow, without evidence of lymphoma. Extended targeted next-generation sequencing revealed wide molecular heterogeneity with MYD88 (14%), PDE4DIP (14%), BIRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A Sleeping Beauty transposonmediated screen identified PDE4DIP as a susceptibility gene for adenomatous polyposis coli (Apc)-dependent intestinal tumorigenesis in mice [15]. PDE4DIP is a commonly mutated gene in leukemia, liver cancer, and nasopharyngeal carcinoma [16][17][18][19], and novel mutations have been reported in tumors originating in various tissues, including the lung, thyroid, ovary [20][21][22], kidney, peritoneum and bone marrow [23][24][25]. Genomic loss/gain and rearrangement of PDE4DIP have been discovered in prostate cancer, glioma, pineoblastoma, and intimal sarcoma [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A Sleeping Beauty transposonmediated screen identified PDE4DIP as a susceptibility gene for adenomatous polyposis coli (Apc)-dependent intestinal tumorigenesis in mice [15]. PDE4DIP is a commonly mutated gene in leukemia, liver cancer, and nasopharyngeal carcinoma [16][17][18][19], and novel mutations have been reported in tumors originating in various tissues, including the lung, thyroid, ovary [20][21][22], kidney, peritoneum and bone marrow [23][24][25]. Genomic loss/gain and rearrangement of PDE4DIP have been discovered in prostate cancer, glioma, pineoblastoma, and intimal sarcoma [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a mutational analysis on bone marrow samples on the 10 patients with confirmed diagnosis, by using a targeted sequencing approach with a 54 myeloid and a 138 lymphoid gene panels on a HiSeq2500 Illumina ( Supplemental Table 1 ). Detailed methods used with each gene panel have been previously published ( 7 , 8 ). Bone marrow mononuclear cells of patients at diagnosis were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Recent genetic studies have provided compelling evidence for an association between PDE4DIP variants and atrial brillation, stroke, and heart failure [21][22][23], but little is known about the biological functions of PDE4DIP in cancers. PDE4DIP alterations are common in human cancers, and mutations, genomic loss/gain, or gene rearrangements of PDE4DIP have been identi ed in multiple tumours, including leukaemia, glioma, pineoblastoma, and prostate cancer [21,[24][25][26][27]. A pancancer analysis revealed that the PDE4DIP gene has potential prognostic and immunotherapeutic value in multiple cancers [28].…”
Section: Introductionmentioning
confidence: 99%